2013
DOI: 10.1007/s11947-013-1072-1
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effectiveness of Sonication, High Shear Mixing and Homogenisation on Improving the Heat Stability of Whey Protein Solutions

Abstract: Upon ultrasonic treatment at 20 kHz, protein aggregates in a dairy whey solution were broken down. In addition, when sonication was applied to a heated solution of denatured and aggregated proteins, there was a dramatic reduction in viscosity and aggregate size, which was maintained after re-heating. This observed heat stability may be due to shear forces that are induced by acoustic cavitation. To determine whether high shear mixing or homogenisation is able to cause similar effects to that of acoustic cavita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 29 publications
2
25
0
Order By: Relevance
“…; Koh et al . ). However, it was observed that the modal distribution for larger particle size (as fat globules) still remained the same as high‐shear mixing only breaks the gel particles from the interaction between protein and fat, with little effect on fat globule size.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Koh et al . ). However, it was observed that the modal distribution for larger particle size (as fat globules) still remained the same as high‐shear mixing only breaks the gel particles from the interaction between protein and fat, with little effect on fat globule size.…”
Section: Resultsmentioning
confidence: 97%
“…Previous researchers have also found that higher mechanical forces (e.g. cavitation, shearing and turbulent flow) could distinctly decrease the droplet size of whipping cream (Long et al 2012;Koh et al 2014). However, it was observed that the modal distribution for larger particle size (as fat globules) still remained the same as high-shear mixing only breaks the gel particles from the interaction between protein and fat, with little effect on fat globule size.…”
Section: Effect Of High-shear Mixing Of Cheese Curdmentioning
confidence: 89%
“…Notably, cavitation-derived shear forces were found to be absent in high-pressure homogenisation. Hence, the study highlighted the fact that the shear forces generated were mainly responsible for the observed particle size reductions even in the absence of cavitational effects [61]. In the case of ultrasound application, the shear forces are resultant from strong bubble collapse.…”
Section: Homogenisationmentioning
confidence: 79%
“…Koh et al [61] used a 20-kHz ultrasonic horn and a high-pressure homogeniser to investigate the particle size reduction of whey protein concentrate (WPC) systems in the presence/absence of cavitational conditions. The particle size reduction in WPC systems under high-pressure conditions showed comparable results when subject to ultrasound under similar energy conditions.…”
Section: Homogenisationmentioning
confidence: 99%
“…-High production costs -Less aseptic processing [23] Lemon myrtle essential oil 97 [15] Sonication Rosemary essential oil 187 -Heat generation during the process due to high shear forces and cavitations [24] Thymus vulgaris essential oil 121 [25] High-pressure homogenization: the use of high-pressure (30-350 MPa) homogenization can reduce an emulsion droplet size to a nanoscale level and improve its stability by the reduction of the creaming rate. In this method, two immiscible liquids along with the used emulsifier are forced to pass through a small orifice where their mixture is subjected to a turbulence and shear flow intense levels [2].…”
mentioning
confidence: 99%